Ipsilateral Simultaneous Low-Energy Multiple Upper Limb Fractures in an Elderly Patient: Case Report and Review of the Literature. (18th May 2022) - Aouad, Dany; Kortbawi, Rabih; Daher, Mohammad; Nehme, Alexandre; Moucharafieh, Ramzi; Badra, Mohammad
Abstract : Traumatic injuries of the upper limb can result in variant fracture combination. This article discusses a rare injury combination including ipsilateral proximal and distal humerus fractures alongside a distal radius fracture. The mechanism of the fall is unknown, but the patient being old with such a complex injury, one can only assume that osteoporosis played a major role. Open reduction and internal fixation was opted for the distal humerus and radius fractures, and percutaneous pinning was done for the proximal humerus fracture. Surgery is an option to each one of these injuries with different techniques available for managing such an association, with emphasis made on osteoporosis workup to help prevent such complex injuries.